Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1017/jfm.2022.28
|View full text |Cite
|
Sign up to set email alerts
|

Near wake interactions and drag increase regimes for a square-back bluff body

Abstract: The three-dimensional near wake of a square-back bluff body in ground proximity is experimentally perturbed by placing a pair of D-shaped obstacles under the body. Five obstacle widths $d$ , from 12 % to 26 % of the height of the body, are used to perform a sensitivity study of the body's pressure drag by varying the relative distance $l$ between the obstacle pair and the base. Two successive drag-sensitive regimes are identified for obstacle-to-base dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
(117 reference statements)
2
6
0
Order By: Relevance
“…However, here, it seems possible that the experimental results were overcorrected by blockage, e.g., the C b of the wW case was corrected from 0.291 (Urquhart et al, 2020) to 0.184 (the reference area here is the projected frontal area including the wheels). The contribution of the base suction to the total drag for the nW model in this study is about 84%, which is higher than the value reported by Varney (2020), but is consistent with that achieved from the experiment of Bao et al (2022). More convincing evidence is that the center of the vortices in the wake fits well in the match between current simulations and the PIV data, as shown in Fig.…”
Section: Resupporting
confidence: 91%
See 3 more Smart Citations
“…However, here, it seems possible that the experimental results were overcorrected by blockage, e.g., the C b of the wW case was corrected from 0.291 (Urquhart et al, 2020) to 0.184 (the reference area here is the projected frontal area including the wheels). The contribution of the base suction to the total drag for the nW model in this study is about 84%, which is higher than the value reported by Varney (2020), but is consistent with that achieved from the experiment of Bao et al (2022). More convincing evidence is that the center of the vortices in the wake fits well in the match between current simulations and the PIV data, as shown in Fig.…”
Section: Resupporting
confidence: 91%
“…Note that less switching occurs in case wW, suggesting a more stable asymmetry state than in case nW. The same trend has also been identified by Bao et al (2022) that the wheels (or the obstacles) have the ability to promote the appearance of bimodal dynamics in some cases. This will be explained in Sec.…”
Section: A Detection Of Wake Bi-stability and Corresponding Wake Topo...supporting
confidence: 75%
See 2 more Smart Citations
“…Previous studies have shown that the wake switching is sensitive to the underbody flow. Experimental studies have triggered wake switching by disturbing the underbody flow, for example using a passive device in the clearance between the body and the ground (Barros et al 2017;Bao et al 2022). Here, we consider that the disturbances in the underbody flow may in part be caused by the interaction of smaller vortices from other surfaces due to the boundary layer dynamics.…”
Section: Unforced Flowmentioning
confidence: 99%